Outcome and Biomarker Analysis from a Multicenter Phase 2 Study of Ipilimumab in Combination with Carboplatin and Etoposide as First‐Line Therapy for Extensive‐Stage SCLC. Issue 9 (September 2016) - Arriola, Edurne; Wheater, Matthew; Galea, Ian; Cross, Nadia; Maishman, Tom; Hamid, Debbie; Stanton, Louise; Cave, Judith; Geldart, Tom; Mulatero, Clive; Potter, Vannessa; Danson, Sarah; et al.
ABSTRACT : Objectives: : Our aim was to evaluate the safety and efficacy of ipilimumab combined with standard first‐line chemotherapy for patients with extensive‐stage SCLC. Methods: : Patients with chemotherapy‐naive extensive‐stage SCLC were treated with carboplatin and etoposide for up to six cycles. Ipilimumab, 10 mg/kg, was given on day 1 of cycles 3 to 6 and every 12 weeks. Response was assessed by the Response Evaluation Criteria in Solid Tumors (RECIST), version 1.0, and immune‐related response criteria. The primary end point was 1‐year progression‐free survival (PFS) according to RECIST. Secondary end points included PFS according to immune‐related PFS and overall survival. Autoantibody serum levels were evaluated and correlated with clinical outcomes. Results: : A total of 42 patients were enrolled between September 2011 and April 2014; 39 were evaluable for safety and 38 for efficacy. Six of 38 patients (15.8% [95% confidence interval (CI): 7.4–30.4]) were alive and progression‐free at 1‐year by RECIST. Median PFS was 6.9 months (95% CI: 5.5–7.9). Median immune‐related PFS was 7.3 months (95% CI: 5.5–8.8). Median overall survival was 17.0 months (95% CI: 7.9–24.3). Of the patients evaluable for response, 21 of 29 (72.4%) achieved an objective response by RECIST and 28 of 33 (84.8%) achieved an objective response by the immune‐related response criteria. All patients experienced at least one adverse event; at least one grade 3 or higher toxicity developed in 35 of 39 patients (89.7%); in 27 patients (69.2%) this was related to ipilimumab. Five deaths were reported to be related to ipilimumab. Positivity of an autoimmune profile at baseline was associated with improved outcomes and severe neurological toxicity. Conclusions: : Ipilimumab in combination with carboplatin and etoposide might benefit a subgroup of patients with advanced SCLC. Autoantibody analysis correlates with treatment benefit and toxicity and warrants further investigation.